PEMANFAATAN SERBUK GERGAJI KAYU UNTUK BUDIDAYA JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DI KELOMPOK MASYARAKAT DESA PASIR KIDUL - Eti Wahyuningsih; Indah Sulistiyawati; Nur Laila Rahayu (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Pasir  Kidul  Village  is  one  of  the  industrial  villages  in  West  Purwokerto  District, Banyumas. Wood industrial waste (pencil factory), namely wood sawdust and wood chips accumulate  and  disturb the surrounding  environment. One of  the uses  of this waste  is  the  raw  material  for  white  mushroom  baglog  (Pleurotus  ostreatus). This Community Partnership Program (PKM) aims to utilize wood sawdust for the cultivation of white oyster mushroom (Pleurotus ostreatus) in community groups in Pasir Kidul Village, West Purwokerto District, Banyumas Regency. This PKM is held for 5 months, from August to December 2018. There are 19 community groups in this community partnership program, with the target that after counseling, training and assistance in the application of "white oyster mushroom cultivation" technology can be applied to 80% of the program participants. The extension stages were training on how to make lemur and baglog for white oyster mushroom cultivation, training on planting seeds and maintaining white oyster mushroom cultivation media, counseling on the influence of types of growing media on white oyster mushroom production, and counseling on environmental factors as determinants of the success of white oyster mushroom cultivation. Some of the problems found by farmers who have carried out cultivation are Baglog sterilization and baglog rot. The results of the community partnership program show that there is an optimization of the utilization of wood sawdust waste which is abundant in the village, by processing wood sawdust into a growing medium for white oyster mushrooms (Pleurotus ostreatus) so that it has a higher useful value and selling value.   Pasir Kidul adalah Kelurahan di Kecamatan Purwokerto Barat, Kabupaten Banyumas, Provinsi Jawa Tengah, Indonesia. Desa Pasir Kidul merupakan salah satu desa industri dengan terdapatnya industri pengolahan kayu (pabrik pensil) yang berdampak langsung dengan melimpahnya limbah padat berupa serbuk gergaji kayu dan serpihan kayu yang terbuang menumpuk di suatu lokasi tertentu yang dapat mengganggu kondisi lingkungan sekitar. Selama ini, serbuk gergaji kayu dibiarkan membusuk, ditumpuk dan dibakar yang berdampak negatif terhadap lingkungan sehingga penanggulangannya perlu dipikirkan. Salah satu upaya untuk membantu mengatasi permasalahan menumpuknya serbuk gergaji kayu di Desa Pasir Kidul adalah pemanfaatan serbuk gergaji kayu untuk budidaya jamur tiram putih (Pleurotus ostreatus) di kelompok masyarakat Desa Pasir Kidul Kecamatan Purwokerto Barat Kabupaten Banyumas. Upaya daur ulang serbuk gergaji kayu yaitu dengan memanfaatkan serbuk gergaji kayu tersebut untuk media tanam jamur tiram putih (Pleurotus ostreatus). Menurut Rachman dan Malik (2011), jika dilihat dari mata rantai industri pengolahan kayu, maka dalam industri penggergajian terjadi proses perubahan kayu pertama kali yaitu kayu dalam bentuk dolok menjadi kayu gergajian (sawn timber) atau disebut juga kayu konversi berupa papan, balok, tiang dan sortimen lainnya.